Boron Analysis and Imaging in BNCT - Agus Permana Putra Sujana (Fakultas Sains dan Matematika Universitas Kristen Satya Wacana, 2020)
Boron Neutron Capture Therapy (BNCT) is a targeted therapy for cancer. BNCT uses boron 10 as media to do targeted therapy, eliminating cancer cell without damaging the surrounding healthy cell. BNCT require support from body imaging to acquire information about the cancer inside patient’s body while the analysis instrumen is use to analyze any parameter relevant to the medication, mainly chemical component of the delivery agents on the therapy and development. Journal divided into 2 , which is imaging and analysis. The imaging also divided into 2 which is imaging that use radioactivity and imaging that doesn’t use radioactivity. Boron analysis group uses analytical instrumentation and methods to gain information about boron outside the bodies ( in sample cell and delivery agents). Body imaging concerned with detecting and gaining information inside the biological object (patient or experiment subject). Information may consist of data about cancer distribution, patient organt condition and boron concentration within biological object.